Effects of corticosteroids and their combinations with hyaluronanon on the biochemical properties of porcine cartilage explants - Puntita Siengdee (2018)
Â© 2015 Siengdee et al. Background: Intra-articular injection of corticosteroids is used to treat the inflammatory pain of arthritis and osteoarthritis (OA), but our previous study found a deleterious effect of these steroids on chondrocyte cells. Hyaluronic acid (HA) injection has been suggested as a means to counteract negative side effects through replenishment of synovial fluid that can decrease pain in affected joints. To better understand the effects of corticosteroids on these processes, dexamethasone (Dex) and prednisolone (Pred) were administered to porcine cartilage explants at several concentrations with and without HA. We examined corticoid effects by determining sulfate-glycosaminoglycan (s-GAG) and uronic acid (UA) content of the explant media, and safranin-O staining of the cells. Analysis of lactate dehydrogenase (LDH) activity was conducted to assess cell cytotoxicity. Results: Dex treatment significantly reduced cellular cytotoxicity compared to the other treatment groups, especially with regards to the release of s-GAG, and protects against superficial proteoglycan damage. However, there was no difference between Pred and Dex, with and without HA, in the UA content remaining in porcine cartilage explants. Conclusions: The data suggest that combinations of Dex and Pred with HA did not have a significant effect on protection or enhancement of the articular cartilage matrix under the current conditions.